Evaluation of the Food Estate Program for Achieving Food Security: Evaluasi Program Food Estate untuk Mencapai Keamanan Pangan - Martani, Rifqi Fakhrian; Bainus, Arry; Rahmatunnisa, Mudiyati (Indonesian Journal of Innovation Studies, 2025)
Background: Indonesia continues to face recurring instability in food availability, marked by fluctuating prices and frequent shortages of staple commodities. Specific background: The Food Estate Program, introduced in 2020, was launched as a large-scale agricultural strategy intended to strengthen national food reserves and reduce vulnerability to supply disruptions. Knowledge gap: Despite extensive discussion, there remains limited integrated analysis comparing policy expectations with actual implementation outcomes across different regions. Aims: This study evaluates the program’s performance in relation to its stated goal of achieving national food security. Results: The evaluation shows that major constraints persist, including land unsuitability for selected crops, environmental degradation, recurrent crop failures, low productivity, inadequate scientific assessments, corporate-centered decision-making, and limited participation of local farmers. Novelty: This research provides a consolidated, multi-site evidence review that highlights disparities between program design and field conditions. Implications: Findings indicate the need for more context-based land evaluation, transparent governance mechanisms, strengthened farmer involvement, and collaboration with independent research institutions to support more coherent pathways toward national food security. Highlights • Program implementation shows clear gaps between planned design and field realities. • Limited farmer involvement contributes to mismatched crop selection and low yields. • Evidence from multiple regions indicates recurring technical and governance challenges. Keywords Food Estate Program, Food Security, Policy Evaluation, Agricultural Governance, Farmer Participation